1994
DOI: 10.1073/pnas.91.20.9514
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of immunotoxin-mediated vascular leak syndrome in rats with retention of antitumor activity.

Abstract: Immunotoxins are hybrid molecules composed of a cell-surface bin domain and a protein toxin moiety that together target sifc cell popaons for elimination. These Vascular leak syndrome (VLS) is the dose-limiting toxicity found in many clinical trials utilizing immunotoxins, including those prepared with blocked ricin, ricin A chain (in native and deglycosylated forms), and saporin (1-10). VLS is characterized in humans by hypoalbuminemia, weight gain, and edema, resulting from the extravasation offluids and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…All patients on our studies receive premedication with dexamethasone, which has been shown to diminish severity of VLS [29,30]. In addition, bolus intravenous fluids are administered before each immunotoxin dose to transiently increase intravascular volume.…”
Section: Vascular Leak Syndromementioning
confidence: 99%
“…All patients on our studies receive premedication with dexamethasone, which has been shown to diminish severity of VLS [29,30]. In addition, bolus intravenous fluids are administered before each immunotoxin dose to transiently increase intravascular volume.…”
Section: Vascular Leak Syndromementioning
confidence: 99%
“…TNF-α and agonistic Fas are known to have also anticancer activity and administration of high dose TNF-α in humans (Schilling et al, 1992) and anti-Fas antibody in mouse (Ogasawara et al, 1993) is reported to cause hepatotoxicity by an unknown mechanism. In mice, an administration of BR96 sFv-PE40 induced no VLS but hepatic injuries (Siegall et al, 1994). In the present study, large administration of pierisin caused only hepatitis-type hepatic injury in mice without showing lymphoid organs injuries.…”
Section: Discussionmentioning
confidence: 59%
“…BR96 sFv-PE40-induced VLS are known to be suppressed by pretreatment of dexamethazone (Siegall et al, 1994) and nonsteroidal antiinflammatory drugs (NASIDs) (Siegall et al, 1997) and but not by histamine or serotonine (Siegall et al, 1994(Siegall et al, , 1997 or not reproduced in athymic rats (Siegall et al, 1994), suggesting a lack of T-cell response. Interleukin-2 (IL-2) induces VLS in mice and tumor necrosis factor-α (TNF-α) plays a central role in their mechanism (Rosenstain et al, 1986;Dubinett et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The efficacy of steroid prophylaxis against PE-induced CLS has been demonstrated in a preclinical model. 77 Weldon et al have reported on an immunotoxin that has a deletion of a large portion of domain II of PE that is fully cytotoxic yet its nonspecific toxicities in mice, which may reflect the ability of these immunotoxins to cause CLS in patients, are greatly diminished. 13 …”
Section: Clsmentioning
confidence: 99%